Promoting campus sustainability through green infrastructure attributes for quality higher education / Muhammad Azhad Azman and Nurul Akmaniza Mohd Nasir - Azman, Muhammad Azhad; Mohd Nasir, Nurul Akmaniza (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The well-being of university students is essential for fostering a supportive and productive learning environment. Throughout their educational journey, students may face various challenges including managing their social interactions, overcoming academic pressures, and navigating personal growth, all while maintaining their physical and mental health. The importance of addressing students' mental health has been highlighted by research, especially in the context of the stress of coursework and adjusting to university life. According to Park S.Y. et al. (2020), academic stress is a significant factor that contribute to the low level of well-being and mental health problems reported by many university students. Exposure to greenery areas has been shown to alleviate stress and reduce depression symptoms (Liu et al., 2022). Therefore, it is critical to ensure that campus green space is properly designed, upgraded and restored to meet the needs of students, with special attention to gender-specific considerations (Foellmer et al., 2021) to enhance the quality of life among university students.